Students' mental health during the pandemic: results of the observational cross-sectional COVID-19 MEntal health inTernational for university Students (COMET-S) study - Fountoulakis, Konstantinos N.; Alias, Nor Aziah; Bjedov, Sarah; Fountoulakis, Nikolaos K.; Gonda, Xenia; Hilbig, Jan; Jakovljević, Miro; Kulig, Barbara; Mahale, Girija; Manafis, Alexandros; Mohammed, Muftau; Nadareishvili, Ilia; et al. (Frontiers in Psychiatry, 2024)
The aim of the study was to search rates of depression and mental health in university students, during the COVID-19 pandemic.This is an observational cross-sectional study. A protocol gathering sociodemographic variables as well as depression, anxiety and suicidality and conspiracism was assembled, and data were collected anonymously and online from April 2020 through March 2021 The sample included 12488 subjects from 11 countries, of whom 9026 were females (72.27 %; aged 21.11±2.53), 3329 males (26.65%; aged 21.61±2.81) and 133 'non-binary gender' (1.06%; aged 21.02±2.98). The analysis included chi-square tests, correlation analysis, ANCOVA, multiple forward stepwise linear regression analysis and Relative Risk ratios Results Dysphoria was present in 15.66% and probable depression in 25.81% of the total study sample. More than half reported increase in anxiety and depression and 6.34% in suicidality, while lifestyle changes were significant. The model developed explained 18.4% of the development of depression. Believing in conspiracy theories manifested a complex effect. Close to 25% was believing that the vaccines include a chip and almost 40% suggested that facemask wearing could be a method of socio-political control. Conspirasism was related to current depression but not to history of mental disorders Discussion The current study reports that students are at high risk for depression during the COVID-19 pandemic and identified specific risk factors. It also suggested a role of believing in conspiracy theories. Further research is important, as it is targeted intervention in students' groups that are vulnerable both concerning mental health and conspiracism.